Bacillus thuringiensis strains effective against insects of Lepidoptera, Coleoptera and Diptera orders - Praça, Lílian Botelho; Batista, Andréa Cardoso; Martins, Érica Soares; Siqueira, Cláudia Brod; Dias, Daniel Gerheim de Souza; Gomes, Ana Cristina Menezes Mendes; Falcão, Rosana; Monnerat, Rose Gomes (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this work was to select among 300 strains of Bacillus thuringiensis those which are simultaneously effective against larvae of Spodoptera frugiperda J.E. Smith and Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae), Anthonomus grandis Boheman (Coleoptera: Curculionidae), Aedes aegypti Linnaeus and Culex quinquefasciatus Say (Diptera: Culicidae). Two strains of B. thuringiensis were selected, S234 and S997, which presented activity against those three insect orders. Both strains were characterized by morphological, biochemical and molecular methods. They have presented two main proteins with 130 and 65 kDa, polimerase chain reaction products with expected sizes for detection of the genes cry1Aa, cry1Ab, cry1Ac, cry1B and cry2 and bipiramidal, cubical and spherical crystals.